Rancang Bangun Prototipe Sistem Parkir Kendaraan Bermotor Dengan Radio Frequency Identification Berbasis Arduino Uno - Musliadi KH; Yonky Pernando (BEES: Bulletin of Electrical and Electronics Engineering, 2023)
Parking management in the city of Mamuju still uses conventional methods which cause many vehicles to park in random places, such as on the shoulder of the road, causing congestion. To overcome this problem, a system is needed to regulate it. This study aims to design a parking system prototype that can later be applied to office centers, shops, shopping and other public places. The results of testing the system prototype by testing registered and unregistered cards, there were no failures in the reading process. It's just that there is a delay of 5 to process data on the registered card. Overall, it can be concluded that the prototype system is functioning properly.